You are on page 1of 2

COMPUTATION

:
Demodulator
Using LSB:

cos ( ω c −ω m ) t

Step 1: after

×

y=cos ( ωC −ωm ) t × cos ( ωc ) t
Let

m ( t )=cos (ω m t)

π
y=co s 2 ( ωc t ) m(t)+sin ( ω c t ) m( t− )cos(ωc t)
4
y=

( 12 + 12 cos (2 ω t )) m ( t ) +sin (ω t ) m(t− π4 )cos (ω t)

y=

( 12 m ( t ) + 12 cos (2 ω t ) m ( t ) )+sin (ω t ) m(t− π4 ) cos(ω t)

c

c

c

Step 2: after

c

c

c

×

y 2=cos ( ωC −ωm ) t × sin ( ω c ) t
Let

m ( t )=cos (ω m t)

π
y 2=cos ( ωc t ) m ( t ) sin(ω c t)+ si n2 ( ωc t ) m(t− )
4
y 2=cos ( ωc t ) m ( t ) sin(ω c t)+

( 12 − 12 cos ( 2 ω t )) m(t− π4 )

y 2=cos ( ωc t ) m ( t ) sin(ω c t)+

( 12 m(t− π4 )− 12 cos (2 ω t ) m(t − π4 ))

c

c

Step 3: after ∑ Before low pass filter: y= ( 12 m ( t ) + 12 cos (2 ω t ) m ( t ) )+sin (ω t ) m(t− π4 ) cos(ω t) c y 2=cos ( ωc t ) m ( t ) sin(ω c t)+ c c ( 12 m(t− π4 )− 12 cos (2 ω t ) m(t − π4 )) c .